2015
DOI: 10.3109/00952990.2015.1049493
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the disapproval and use of marijuana among adolescents and young adults in the United States: 2002–2013

Abstract: Background Despite policy changes related to the use and distribution of marijuana in cities and states across the country, few studies have examined changes in disapproval and use of marijuana among American youth. Objectives To examine trends in disapproval and use of marijuana among adolescents and young adults in the United States. Method We employ nationally representative data spanning the period of 2002–2013. Analyses are based on self-reported measurements from 105,903 younger adolescents (ages 12–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
44
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 15 publications
13
44
1
2
Order By: Relevance
“…For instance, our research on marijuana trends using the NSDUH data found that the proportion of young adults (ages 18 to 25) reporting disapproval of marijuana use dropped by more than 25% between 2002 and 2013 [9]. While we did not observe a large trend increase in marijuana use among young adults, other studies seem to indicate that adult marijuana use is on the rise.…”
contrasting
confidence: 77%
See 1 more Smart Citation
“…For instance, our research on marijuana trends using the NSDUH data found that the proportion of young adults (ages 18 to 25) reporting disapproval of marijuana use dropped by more than 25% between 2002 and 2013 [9]. While we did not observe a large trend increase in marijuana use among young adults, other studies seem to indicate that adult marijuana use is on the rise.…”
contrasting
confidence: 77%
“…Evidence from the National Youth Risk Behavior Survey (YRBS) and Monitoring the Future (MTF) suggests that marijuana use among adolescents has decreased slightly over the last two decades [7,8]. Our research using data from the National Survey on Drug Use and Health (NSDUH) also points to decreases in marijuana use among adolescents between 2002 and 2013 [9]. However, contrary to Fleming et al, we did not observe an increase in marijuana-related risk factors among adolescents (at least not the risk factors we examined); indeed, we found a meaningful increase in disapproval of youth marijuana use among adolescents ages 12 to 14 and found that disapproval remained stable among adolescents age 15 to 17.…”
mentioning
confidence: 67%
“…Our approach is also consistent with high-cited trend studies (Ogden et al, 7 2006) as well as recent trend studies that utilized NSDUH data (Salas-Wright, Vaughn, Todic, Córdova, & Perron, 2015). Prevalence estimates and their corresponding 95% confidence intervals were computed using functions from the "survey" package in R (R Core Team, 2015).…”
Section: Statistical Analysessupporting
confidence: 56%
“…This approach follows the trend analysis method outlined by the Centers for Disease Control and Prevention (2014). This approach is also consistent with highly-cited trend studies (Ogden et al, 2006) as well as recent trend studies that utilized NSDUH data (Salas-Wright, Vaughn, Todic, Córdova, & Perron, 2015). Prevalence estimates and their 95% confidence intervals were calculated using logistic regression functions within the 'survey' package in R (R Core Team, 2015).…”
Section: Statistical Analysesmentioning
confidence: 76%